2132. Infections After Pediatric Ambulatory Surgery: Incidence and Risk Factors. (26th November 2018) - Gerber, Jeffrey S; Ross, Rachael; Xiao, Rui; Localio, A Russell; Grundmeier, Robert; Rettig, Susan; Teszner, Eva; Szymczak, Julia E; Canning, Douglas; Coffin, Susan E
Abstract: Background: Approximately 3 million pediatric ambulatory surgical procedures are performed each year in the United States; however, little is known about the incidence of and risk factors for surgical site infections (SSI) after pediatric surgical procedures performed in these settings. Therefore, we aimed to describe the epidemiology of SSI in children after ambulatory surgery. Methods: We conducted a prospective, observational study in a single healthcare network with three ambulatory surgical facilities (ASF) and one hospital-based facility. We enrolled children <18 years who had an ambulatory surgical procedure between June 2012 and December 2015. Data on follow-up care were collected via a structured telephone interview (30–45 days post-surgery) and review of the electronic health record (EHR) 60 days post-surgery. We identified SSIs 30 days after surgery by applying 2010 National Healthcare Safety Network (NHSN) definitions. We also developed a broader definition of possible infectious events associated with surgery up to 60 days after surgery. Results: We enrolled 8, 502 surgical encounters; 64% occurred at the hospital-based facility. Three procedure categories (soft tissue excision, hernia, scrotal/testicular) accounted for 56% of encounters at ASFs. We identified 21 NHSN defined SSIs (2.5 SSIs per 1, 000 surgical encounters). In adjusted analysis, there was no difference between hospital-based facility and ASF SSI rates (OR 0.7; 95% CI 0.2–2.3). Using the broader definition, we identified 404 surgical encounters with strong or some evidence of possible infection (48 per 1, 000 surgical encounters). There was poor agreement of possible infections identified via parent interview vs. EHR. In multivariable analysis using the broader definition, older age and black race were associated with a reduced risk. Conclusion: Using a rigorous surveillance definition, the incidence of surgical site infections was low after pediatric ambulatory surgery although our data suggest there may be additional infectious complications that are not captured by the NHSN definition. Given the annual rate of pediatric ambulatory surgery, even a low rate of infection may result in a significant medical burden. Disclosures: All authors: No reported disclosures.